1999
DOI: 10.1177/088532829901400103
|View full text |Cite
|
Sign up to set email alerts
|

The Antithrombotic versus Calcium Antagonistic Effects of Polyethylene Glycol Grafted Bovine Pericardium

Abstract: Cardiovascular calcification, the formation of calcium phosphate deposits in cardiovascular tissue, is a common end stage phenomenon affecting a wide variety of bioprosthesis. This study proposes a novel approach of reducing pericardial calcification and thrombosis via coupling polyethylene glycols (PEG) to glutaraldehyde treated bovine pericardium via acetal linkages. The calcification of the PEG modified tissue and the control pericardium (extracted and glutaraldehyde treated) was investigated by in vivo rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Administration of compounds that release NO attenuates vasoconstriction, lack of capillary perfusion, leukocyte adhesion, and edema in I/R injury (5). In addition, I/R injury increases coagulation by activating endothelial cells to produce von Willebrand factor (vWF) during I/R, probably through increased production of free radicals and enhanced shear stress early in reperfusion (16,33,37). Arte-riolar shear stress decreases during reperfusion, suggesting that I/R could alter mechanotransduction in the endothelium via damage to NO formation (6, 8 24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of compounds that release NO attenuates vasoconstriction, lack of capillary perfusion, leukocyte adhesion, and edema in I/R injury (5). In addition, I/R injury increases coagulation by activating endothelial cells to produce von Willebrand factor (vWF) during I/R, probably through increased production of free radicals and enhanced shear stress early in reperfusion (16,33,37). Arte-riolar shear stress decreases during reperfusion, suggesting that I/R could alter mechanotransduction in the endothelium via damage to NO formation (6, 8 24).…”
mentioning
confidence: 99%
“…Moreover, PEG interferes with the coagulation system and reduces platelet adhesion in vitro and in vivo (3,15). PEG forms a molecular barrier on the glycocalyx, preventing acute platelet deposition on damaged arteries, and grafting of pericardium with PEG inhibits calcium deposits and reduces adhesion of platelets and leukocytes to the surface (12,37). Therefore, by application of PEG with end groups reactive to protein-free amine to improve biostability, it is possible to reduce inflammation and control water content of endothelial cells (28,32,38).…”
mentioning
confidence: 99%
“…2) showed adhered platelets, calcified areas, and markable breakdown of collagen bundles whereas reduced platelet adhesion, calcification, and enzymatic digestion were observed on PEG grafted BP coimplanted with the aspirin/heparin loaded co‐matrix. However, our previous in vitro and in vivo observations (24) have proven that PEG grafting on the pericardium reduces chances for calcification and enzymatic attack. Aspirin/heparin delivery on PEG modified BP further improved the stability of the pericardial tissue and produces a blood‐compatible and anticalcifying interface.…”
Section: Resultsmentioning
confidence: 96%
“…A small number of researchers have investigated the filling of interstitial void spaces in GA pre-treated tissue with a macromolecular substance in order to prevent calcification, with the belief that some of the following mechanisms may be involved: (i) reaction of macromolecules with free aldehyde groups of GA to inactivate them [22], (ii) the formation of a barrier that prevents the release of residual GA [23], (iii) exclusion of host-plasma calcium [24] and phospholipids [8] by filling inter-tropocollagen spaces, (iv) blocking of potential nucleation sites for the growth of hydroxyapatite crystals [22], (v) masking of platelet receptor sites on collagen so that platelet attachment and aggregation is prevented [25] and (vi) increasing hydrophilicity with subsequent reduction in protein adsorption and platelet adhesion [26]. Taira et al used acrylamide (AAm) gels for in vitro investigations, and suggested a mechanism whereby the penetration of putative serum-derived inhibitors of calcification affect calcium deposition [27].…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo properties of pAAm is highlighted by the fact that no signs of degradation, granulomas, inflammation or fibrosis were observed in clinical cases after the 10-year follow-up of breast augmentation procedures using pAAm [28]. The use of chitosan [22,23], heparin [24] and poly(ethylene glycol) (PEG) [25,29] as space-filling materials in GA pre-fixed tissue, has also been reported.…”
Section: Introductionmentioning
confidence: 99%